1989
DOI: 10.1002/chp.4750090410
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of grand rounds in continuing medical education

Abstract: Grand Rounds activities are an integral component of medical education. They present clinical problems in medicine by focusing on current or interesting cases. Grand Rounds originated as part of residency training wherein new information was taught and clinical reasoning skills were enhanced. Today, Grand Rounds also are used in continuing medical education as an instructional method for maintaining and improving clinical skills of practicing physicians. This study reviewed 43 Grand Rounds activities conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 6 publications
0
18
0
1
Order By: Relevance
“…This could be addressed through a variety of approaches including lectures, problem-based learning, didactic sessions, journal club conferences, and grand rounds presentations. [8][9][10][11][12] Programs could also invite acknowledged experts to lecture at their institutions. Residents in programs lacking skin of color training may also benefit from externships to increase exposure to diseases in patients with skin of color.…”
Section: Discussionmentioning
confidence: 99%
“…This could be addressed through a variety of approaches including lectures, problem-based learning, didactic sessions, journal club conferences, and grand rounds presentations. [8][9][10][11][12] Programs could also invite acknowledged experts to lecture at their institutions. Residents in programs lacking skin of color training may also benefit from externships to increase exposure to diseases in patients with skin of color.…”
Section: Discussionmentioning
confidence: 99%
“…Originally a patient-centered experience aimed at increasing clinician knowledge for treating unique cases, today Grand Rounds is more commonly used to educate students, showcase faculty role models, and promote collegiality in clinical settings (Herbert & Wright, 2003;Hull et al, 1989). As model of delivering experiential learning opportunities, the Grand Rounds forum has been used as an important mechanism for teaching new information, facilitating clinical reasoning skills, and enhancing competency among clinicians (Hull et al, 1989;Van Hoof, Monson, Majdalany, Giannotti, & Meehan, 2009). Participation in Grand Rounds has also been associated with increased flexibility in thinking and memory for clinical knowledge (Praschinger, Steiger, & Kainberger, 2007).…”
Section: Grand Rounds: a Model For Clinical Trainingmentioning
confidence: 99%
“…Each element of the multicultural Grand Rounds is intended to illuminate the roles of cultural factors affecting professionals in the practice of clinical psychology. Prior research suggests that Grand Rounds events facilitate professional competency, including clinical knowledge and decision-making (Hull et al, 1989;Praschinger et al, 2007;Van Hoof et al, 2009). A particularly engaging and important benefit of the Grand Rounds forum is the spontaneity of the panel-student discussion regarding ways to adapt clinical interventions to meet the needs of culturally diverse patients.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…6,7 One study demonstrated that when the adult education program planning requirements of the Accreditation Council for Continuing Medical Education requirements were applied, an improvement of educational outcomes resulted. 4 A more recent study of teaching hospitals in Calgary, Alberta, 8 reported that formal grand rounds accounted for more than 2,000 hours per year. Grand rounds were viewed as the main hospital-based continuing education activity.…”
Section: Introductionmentioning
confidence: 99%
“…For the same decade, the authors of the U.S. study concluded that medical grand rounds were considered important in most academic medical centers but that, generally, the popularity of rounds was felt to have decreased. Outcomes used in a variety of evaluation studies have included participant satisfaction and attendance, 2,3 perceptions of importance and educational purpose, 3,4 knowledge gain and retention, 5 and prescribing practices. 6,7 One study demonstrated that when the adult education program planning requirements of the Accreditation Council for Continuing Medical Education requirements were applied, an improvement of educational outcomes resulted.…”
Section: Introductionmentioning
confidence: 99%